Both JNK1 and JNK2 Are Indispensable for Sensitized Extracellular Matrix Mineralization in IKKβ-Deficient Osteoblasts - Hao, Qianyun; Liu, Zhuangzhuang; Lu, Liaoxun; Zhang, Lichen; Zuo, Li (Frontiers in Endocrinology, 2020)
Extracellular matrix mineralization is critical for osteogenesis, and its dysregulation could result in osteoporosis and vascular calcification. IKK/NF-κB activation inhibits differentiation of osteoblasts, and reduces extracellular matrix mineralization, however the underlying mechanisms are poorly understood. In this study, we used CRISPR/Cas9 system to permanently inactivate IKKβ in preosteoblast cells and confirmed that such cells displayed dramatic increase in extracellular matrix mineralization associated with JNK phosphorylation. Such observation was also found in our study using IKKβ-deficient primary murine osteoblasts. Interestingly, we found that in Ikbkb−/− Mapk8−/− or Ikbkb−/− Mapk9−/− double knockout cells, the enhanced mineralization caused by IKKβ deficiency was completely abolished, and deletion of either Mapk8 or Mapk9 was sufficient to dampen c-Jun phosphorylation. In further experiments, we discovered that absence of JNK1 or JNK2 on IKKβ-deficient background resulted in highly conserved transcriptomic alteration in response to osteogenic induction. Therefore, identification of the indispensable roles of JNK1 and JNK2 in activating c-Jun and promoting osteoblast differentiation on IKKβ-deficient background provided novel insights into restoring homeostasis in extracellular matrix mineralization.